Response of Citrus aurantium L. orange seedlings to the addition of NPK complex nanofertilizer and humic and their effect on vegetative traits and nutrients. - Hamid Hammood Mahawesh (University of Thi-Qar Journal of agricultural research, 2023)
The study was carried out at University of Thi-Qar on 02.02.2023; the experience finished on 15.06.2023 on Citrus seedlings at one year age, by three seedlings for each experimental unit. Thus the number of seedlings was 81 at anvils plastic, which was filed by soil and peatmoss at a ratio of 3:1. The experiment included fertilizer treatment Nano NPK which spray on plant leaves at concentrations (0, 0.5, 1) g. l, by three additions at 15 days period between each addition. Humic acid was added to the Spray the plant three times (0, 1, 2) g. The experiment was carried out by three replication according to Randomized Complete Block Design (RCBD). The results were compared according to less difference test than 5 % possibility.Spraying treatments with nano-fertilizer npk showed a positive effect on most of the vegetative and chemical indicators of orange seedlings. The spraying treatment at a concentration of 1 gm l-1 was significantly superior by recording the highest rate for the number of plant leaves, stem thickness, leaf content of carbohydrates, and leaf content of the nutrients calcium, magnesium, and sulfur. It reached 61.78 leaves. Seedling-1, 7.77 cm, 10.21%, 155.62%, 0.268%, 38.046%, respectively.The average spray treatments with Humic showed a positive effect on most of the vegetative and chemical indicators of Citrus aurantium L. orange seedlings. The spray treatment at a concentration of 1 gm L-1 was superior in recording the highest rates for the number of plant leaves and stem thickness, as they reached 64.78 and 8.77, respectively. The spraying treatment at a concentration of 1 gm L-1 also excelled by recording the highest rate for the leaf content of carbohydrates and the leaf content of the nutrients calcium, magnesium and sulfur, reaching 10.01%, 156.53%, 0.257%, 36.06%. The interaction treatments between the two study factors gave a positive, significant effect on most of the vegetative and chemical traits studied. The interaction treatment between the concentration of 1 gm L-1 of nano-NPK and 1 gm L-1 Humic recorded the best results significantly for growth indicators.